Tuberous Sclerosis Complex: A Case Report - Areej Riaz, Rabia Chaudary (Pakistan Journal of Ophthalmology, 2018)
Tuberous sclerosis complex is an uncommon neurocutaneous syndrome characterized by development of benign tumors affecting multiple body systems including skin, brain, retina and viscera. The management of these patients is multidisciplinary, involving specialists from different fields. Since it can present with a wide range of manifestations, the quality of life and prognosis depends on the particular abnormalities seen in a patient. Here, we report a case of an 11 year old boy with typical clinical and radiological features of tuberous sclerosis. Key Words: adenoma sebaceum, subependymal giant cell astrocytoma, nonrenal hamartoma.